Oscillatory local field potentials of the nucleus accumbens and the anterior limb of the internal capsule in heroin addicts. Issue 6 (June 2018) - Ge, Shunnan; Geng, Xinyi; Wang, Xuelian; Li, Nan; Chen, Lei; Zhang, Xinjing; Huang, Yongzhi; Li, Yang; Chen, Yukun; Wang, Shouyan; Gao, Guodong
Highlights: The features of power spectra for local field potentials (LFPs) of the nucleus accumbens (NAc) and anterior limb of the internal capsule (ALIC) in heroin addicts were studied. LFP theta power in ALIC and alpha power in NAc correlated with craving and depression. Neural activity in dorsal and ventral striatum were mainly coordinated within the low-frequency band. Abstract: Objectives: The nucleus accumbens (NAc) is known to regulate the motivation and underlie addictive behaviors, and the anterior limb of the internal capsule (ALIC) is involved in several psychiatric disorders. Our study aimed to explore the functions of NAc and ALIC electrophysiologically. Methods: The local field potentials (LFPs) of the NAc and ALIC were recorded from 7 heroin addicts treated with deep brain stimulation. Correlation analysis was made between LFP powers in various frequency bands and the subjects' neuropsychological test scores; coherence was calculated for the LFPs in NAc and ALIC. Results: Both the NAc and ALIC exhibited prominent theta and alpha frequency band activity in the LFP power spectra. Additionally, a distinct beta band peak was detected in the power spectra of ALIC LFPs, which may represent the activity of striatal bridge cells. There was a significant negative correlation between the power of the theta frequency band of ALIC LFPs and visual analogue scale (VAS) scores indicative of cravings (Spearman's ρ  = −0.758, P  = 0.002), and a significant positive correlation was found between the power of the alpha frequency band of NAc LFPs and subjects' scores on the Hamilton depression inventory ( ρ  = 0.727, P  = 0.005). LFPs of the NAc and ALIC exhibited higher coherence values in the theta and alpha frequency bands. Conclusions: The results suggest that theta power in the ALIC/dorsal striatum and alpha power in the NAc may be associated with drug cravings and depressive symptoms, respectively, in heroin addicts. For these subjects, the neural activities in the dorsal and ventral striatum were mainly coordinated within the low-frequency band. Significance: The study illustrates the neurophysiologic characteristics of heroin addiction and its comorbidities, providing a potential theoretical basis for optimizing deep brain stimulation (DBS) therapy.